Development of low-cost bio-adsorbent from agricultural waste composite for Pb(II) and As(III) sorption from aqueous solution. Issue 1 (1st January 2019) - Obayomi, K. S.; Bello, J. O.; Nnoruka, J. S.; Adediran, A. A.; Olajide, P.O
Abstract: Agricultural waste composite-activated carbon was developed and characterized by means of chemical activation (KCl) to be utilized for the uptake of Pb(II) and As(ll) in a batch adsorption process. This study was carried out to minimize the widespread of heavy metals within water source. Batch adsorption studies were carried out with the consideration of factors such as pH, temperature, initial concentration, adsorbent dosage and contact time. The phase identification (XRD), surface chemistry (FTI-IR), surface area (BET), surface morphology and elemental identification (SEM/EDX) were all investigated in this study, and the BET surface area were 230.242 and 849.630 m 2 /g resulting in relatively high adsorption capacities of 200 and 250 mg/g for both As(lIl) and Pb(II), respectively. The adsorption rate of Pb(II) and As(III) onto AWCAC was faster in the first 30 min but it attained equilibrium at 90 min for both metal ions. The Isotherm models studied show that the adsorption process was fitted best to Langmuir model. The result of the kinetic and thermodynamic studies revealed that the adsorption process followed a pseudo-second-order, physical, exothermic, and spontaneous in nature. The adsorption of As(III) and Pb(II) unto agricultural waste composite when compared with other adsorbents in literature gave the highest adsorption capacity.